High performance control of AC drives with MATLAB/Simulink models - Abu-Rub, Haithem; Iqbal, Atif.; Guzinski, Jaroslaw (Chichester, West Sussex : Wiley, 2012)
"This book will provide an initial guideline to students and professionals. It focuses on the advanced control of AC machines and will keep the readers abreast with the latest technology"--
Front Matter -- Introduction to High Performance Drives -- Mathematical and Simulation Models of AC Machines -- Pulse Width Modulation of Power Electronic DC-AC Converter -- Field Oriented Control of AC Machines -- Direct Torque Control of AC Machines -- Non-Linear Control of Electrical Machines Using Non-Linear Feedback -- Five-Phase Induction Motor Drive System -- Sensorless Speed Control of AC Machines -- Selected Problems of Induction Motor Drives with Voltage Inverter and Inverter Output Filters -- Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: MATLAB; SIMULINK; MATLAB; SIMULINK; MATLAB; SIMULINK; MATLAB; SIMULINK; Electric motors, Alternating current -- Computer simulation; Electric motors, Alternating current -- Automatic control; Electric motors, Alternating current -- Computer simulation; Electric motors, Alternating current -- Automatic control; SCIENCE -- System Theory; Electric motors, Alternating current / Computer simulation; Electric motors, Alternating current / Automatic control; Electronic books; Electronic books